2016
DOI: 10.1111/zsc.12228
|View full text |Cite
|
Sign up to set email alerts
|

An integrative approach to the evolution of shrimps of the genus Palaemon (Decapoda, Palaemonidae)

Abstract: Shrimps of the genus Palaemon Weber, 1795 comprise of 86 species with a wide morphological and ecological variability along the tropical and temperate regions. Studies based on molecular data have indicated that despite a recent taxonomic rearrangement, it may remain not monophyletic. On the other hand, cladistic, morphological analyses have suggested the presence of synapomorphies, implying a natural status for the genus. In this work, a broad taxonomic and molecular sampling is applied to verify whether Pala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…The genus Macrobrachium comprises over 200 freshwater prawns globally distributed across tropical and subtropical regions [66]. Carvalho et al [8] already reported that Palaemon species with freshwater phases exhibited a closer relationship with the genus Macrobrachium than to other Palaemon species, and were included in one of the three clades identified within Palaemon, the 'Alaocaris' clade. Consequently, P. capensis may be included in the 'Alaocaris' clade as is an amphidromous shrimp [67].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…The genus Macrobrachium comprises over 200 freshwater prawns globally distributed across tropical and subtropical regions [66]. Carvalho et al [8] already reported that Palaemon species with freshwater phases exhibited a closer relationship with the genus Macrobrachium than to other Palaemon species, and were included in one of the three clades identified within Palaemon, the 'Alaocaris' clade. Consequently, P. capensis may be included in the 'Alaocaris' clade as is an amphidromous shrimp [67].…”
Section: Plos Onementioning
confidence: 99%
“…Therefore, molecular data could be crucial to elucidate taxonomic ambiguities. Indeed, the family Palaemonidae has been the subject of numerous systematic and evolutionary studies due to its wide geographical distribution, large variety of habitats and the economic importance of some species [8]. Specifically in Palaemon, extensive worldwide phylogenetic analyses have been performed revealing the need for further systematic rearrangements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, phylogenetic and taxonomic revisions changed the status of the genus Palaemon [811] as well as the number of its species. The genus Palaemon currently comprises 86 species, two of which have been recently described ( Palaemon minos sp.…”
Section: Introductionmentioning
confidence: 99%
“…Crustaceans in particular, represent an excellent group for investigating this question in a greater detail because they represent one of the most diversified groups (67,000 recognized species), that occur in all types of aquatic habitats (fresh to sea water), with distinctive phenotypic traits apparent between freshwater and saltwater inhabitants (Vogt, 2013;Carvalho et al, 2016). In some instances, even different con-specific populations have been observed to tolerate different ranges of environmental salinity (Moshtaghi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%